2019
DOI: 10.3390/ijerph16081421
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilator Response Predicts Longitudinal Improvement in Small Airway Function in World Trade Center Dust Exposed Community Members

Abstract: The evolution of lung function, including assessment of small airways, was assessed in individuals enrolled in the World Trade Center Environmental Health Center (WTC-EHC). We hypothesized that a bronchodilator response at initial evaluation shown by spirometry or in small airways, as measured by forced oscillation technique (FOT), would be associated with improvement in large and small airway function over time. Standardized longitudinal assessment included pre and post bronchodilator (BD) spirometry (forced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…We defined our study population to include those with normal spirometry values. We and others have previously reported the association of small airway dysfunction with symptoms and exposures in many WTC-exposed community members with preserved spirometry [ 16 , 35 , 43 , 44 , 67 ] and we therefore hypothesized that persistent respiratory symptoms would be associated with increased small airway dysfunction in this study. The median values for all measures of forced oscillation, including those considered to assess small airway function (R5–20), were slightly elevated (abnormal) in the group as a whole.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We defined our study population to include those with normal spirometry values. We and others have previously reported the association of small airway dysfunction with symptoms and exposures in many WTC-exposed community members with preserved spirometry [ 16 , 35 , 43 , 44 , 67 ] and we therefore hypothesized that persistent respiratory symptoms would be associated with increased small airway dysfunction in this study. The median values for all measures of forced oscillation, including those considered to assess small airway function (R5–20), were slightly elevated (abnormal) in the group as a whole.…”
Section: Discussionmentioning
confidence: 93%
“…Controlled patients ( Table 3 ). We used a normal value of R 5 as < 3.96 cmH 2 O/L/s [ 33 , 34 , 35 ] and we considered a normal value of R 5–20 to be < 0.76 cmH 2 O/L/s based on previously published data [ 33 , 34 , 35 ]. There was a suggestion of an elevated median pre- and post-BD R 5–20 in Uncontrolled participants compared with Controlled, although this did not reach statistical significance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of cleaning practices by residents in lower Manhattan showed that cleaning with dry methods was associated with more types of respiratory symptoms than other cleaning methods (Antao, 2019 [3]). Other papers delved into the underlying physical and biological aspects of pulmonary illness among persons exposed to 9/11 (Liu, 2019 [5]; Kwon, 2019 [6]; Pradhan, 2019 [7]). Liu et al (2019) used chest tomography (CT) and reported that firefighters with high intensity exposure on 9/11 had increased risk of bronchial wall thickening, emphysema, and air trapping.…”
mentioning
confidence: 99%
“…They reported that given 9/11 exposure, having three or more MSBs increased airway hyperactivity beyond that associated with 9/11 exposure. Another paper that evaluated the bronchodilator response among community members exposed to 9/11 found that a proportion of small airway problems were irreversible, which was predicted by the bronchodilator response at initial visits (Pradhan, 2019 [7]). Two other papers evaluated the increased risk of asthma control issues and quality of life as a function of indoor allergens (Rojano, 2019 [8]) and air pollution/irritants (Yung, 2019 [9]).…”
mentioning
confidence: 99%